identité du mois de mars 2020

Posté le : lundi 2 mars 2020 par Vincent Thill

x = (3^n)[(2b-2a)(2a)^{(2n+1)}+(-b^2-2a)b^{(2n+1)}+(-b-2a)(b-2a)^{(2n+1)}]

y = 2a(2b-2a)^{(2n+1)}+b(b-4a)^{(2n+1)}+(b-2a)(-b-2a)^{(2n+1)}

x = y      lorsque   a = b( b + 1 )/( 2 )        ceci pour  n = 1, 2, 3, 4

__________________________________________________

x = (3^n)[(6b-2a)(2a)^{(2n+1)}-(3b^2-2a)(3b)^{(2n+1)}+(-3b-2a)(3b-2a)^{(2n+1)}]

y = 2a(6b-2a)^{(2n+1)}-3b(3b^2-2a)^{(2n+1)}+(3b-2a)(-3b-2a)^{(2n+1)}

x = y     lorsque   a = b( b + 1 )/( 2 )       ceci  pour  n = 1, 2, 3, 4

___________________________________________________

x = (3^n)[9a(a-4b)^{(2n+1)}+(6b-6a)(4b+2b^2)^{(2n+1)}+(3a+6b)(5a-2b)^{(2n+1)}]

y = (4a+2b)(6b-6a)^{(2n+1)}+(5a-2b)(3a+6b)^{(2n+1)}+(a-4b)(9a)^{(2n+1)}

x = y     lorsque   a = b( b + 1 )/( 2 )     ceci   pour  n = 1, 2, 3, 4

___________________________________________________

x = (6b-2a)(2a)^9-(3b^2-2a)(3b)^9+(-3b-2a)(3b-2a)^9

y = (6b-2a)(2a)^5-(3b^2-2a)(3b)^5+(-3b-2a)(3b-2a)^5

z = (6b-2a)(2a)^7-(3b^2-2a)(3b)^7+(-3b-2a)(3b-2a)^7

4xy = 3z²        lorsque     a = b( b + 1 )/( 2 )

____________________________________________________

x = 2a(6b-2a)^9-3b(3b^2-2a)^9+(3b-2a)(-3b-2a)^9

y = 2a(6b-2a)^5-3b(3b^2-2a)^5+(3b-2a)(-3b-2a)^5

z = 2a(6b-2a)^7-3b(3b^2-2a)^7+(3b-2a)(-3b-2a)^7

4xy = 3z²     lorsque    a = b( b + 1 )/( 2 ) .

Tags:

Les commentaires sont fermés